Experimentos com formulações de programação inteira para o problema do permutation flowshop - Santos, Gerson Garcia dos (2008)
The Permutation Flowshop problem is one of the most well-known problems in the field of scheduling and has been intensely explored since the 1950s. The present work brings two contributions for the study of this problem in the context of integer programming. The first is an experimental evaluation of the effect of some branch rules (inspired in Potts rule proposed in the 1980s) in the performance of a branch-and-bound algorithm over the classic Wilson s formulation. The second contribution is the analysis of a new formulation whose linear relaxation yields better lower bounds than the Wilson s formulation does.